Impacts of climate change adaptation options on soil functions: A review of European case‐studies - Hamidov, Ahmad; Helming, Katharina; Bellocchi, Gianni; Bojar, Waldemar; Dalgaard, Tommy; Bahadur Ghaley, Bhim; Hoffmann, Christian; Holman, Ian P.; Holzkämper, Annelie; Krzeminska, Dominika; Kværnø, Sigrun H.; Lehtonen, Heikki; et al. (Cranfield University, 2018)
Soils are vital for supporting food security and other ecosystem services. Climate change can affect soil functions both directly and indirectly. Direct effects include temperature, precipitation, and moisture regime changes. Indirect effects include those that are induced by adaptations such as irrigation, crop rotation changes, and tillage practices. Although extensive knowledge is available on the direct effects, an understanding of the indirect effects of agricultural adaptation options is less complete. A review of 20 agricultural adaptation case‐studies across Europe was conducted to assess implications to soil threats and soil functions and the link to the Sustainable Development Goals (SDGs). The major findings are as follows: (a) adaptation options reflect local conditions; (b) reduced soil erosion threats and increased soil organic carbon are expected, although compaction may increase in some areas; (c) most adaptation options are anticipated to improve the soil functions of food and biomass production, soil organic carbon storage, and storing, filtering, transforming, and recycling capacities, whereas possible implications for soil biodiversity are largely unknown; and (d) the linkage between soil functions and the SDGs implies improvements to SDG 2 (achieving food security and promoting sustainable agriculture) and SDG 13 (taking action on climate change), whereas the relationship to SDG 15 (using terrestrial ecosystems sustainably) is largely unknown. The conclusion is drawn that agricultural adaptation options, even when focused on increasing yields, have the potential to outweigh the negative direct effects of climate change on soil degradation in many European regions.
Keywords: agricultural adaptation; DPSIR; regional case studies; soil degradation; Sustainable Development Goals